Evaluasi Data Peresepan Elektronik di Pu skesmas Gunung Kidul Tahun 2011 - , Zakiyah Oktafiani; , dr. Lutfan Lazuardi, M.Kes, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Community health center is spearheading the government's efforts in providing health services in the community. In organizing these efforts should be supported by information systems that facilitate the process of recording and data processing. Monitoring the results of management information systems, especially in electronic prescribing community health centers of Gunung Kidul need to be assessed, the views from the prevention of medication errors, duplication of drug therapy, and drug interactions picture. With the aim of research was made on the Electronic Prescribing Data Evaluation in Community Health Centers of Gunung Kidul During 2011. Information system evaluation method used is HOT-Fit. The qualitative data obtained from interviews conducted descriptive and applied prospectively. The study is limited by collecting data from the electronic prescription 10 disease indications with the highest prevalence in 2011 with a sample of 1200 recipes. This research is non-experimental descriptive using retrospective method. Data taken by Random Sampling. From interviews regarding evaluation pharmacy management information system as a whole is pretty good. Use of information systems, especially in electronic prescribing in general can prevent the occurrence of Medication Error. Duplication of therapy in prescribing occurred in 15 recipes. Drug interactions occur in 48 recipes. Evaluation of the results of the overall prescribing see a trend in the use of drugs known as corticosteroids.